Talqin Strategy and Qur’anic Memorization in Non–Full Tahfidz Islamic Boarding Schools - Ahmad Habibi; Chusnul Muali (JURNAL ISLAM NUSANTARA, 2025)
This study aims to examine the implementation and effectiveness of the talqin strategy in strengthening Qur’anic memorization in non–full tahfidz Islamic boarding schools. Qur’anic memorization remains a core element of Islamic education, yet many pesantren face limited instructional time and systemic constraints that undermine the quality of memorization. These conditions necessitate adaptive pedagogical strategies that maintain accuracy, retention, and student engagement. This research employed a qualitative multi-site case study conducted at two pesantren, using observations, in-depth interviews, and documentation. Data were analyzed through an interactive thematic model to capture cognitive, affective, and systemic dimensions of learning. The findings reveal that talqin significantly enhances the cognitive and technical quality of memorization by strengthening auditory encoding, retention stability, and recitational accuracy. It also positively influences students’ affective domain by increasing confidence, motivation, and learning readiness through guided correction and emotional reassurance. Furthermore, the effectiveness of talqin is powerfully shaped by instructional systems, teacher supervision, student preparedness, and institutional learning culture. These results demonstrate that talqin functions as a system-dependent pedagogical strategy rather than a standalone technique. This study contributes theoretically by offering a holistic model of Qur’anic memorization and, practically, by recommending a structured, supervised, and context-sensitive implementation of talqin in pesantren with limited tahfidz programs.